EFL Students’ Practices in Exploring Digital Comics: Extensive Reading Activities at English Club - Muhammad Rizky Sholehudin (Retain: Journal of Research in English Language Teaching, 2025)
English language skills have become one of the crucial things for learning in Education. Extensive reading activities are an important way for students can develop their English comprehension. In addition, this extensive reading activity can be collaborated using several reading media. Digital comics can be used for reading media, where these digital comics have attractive visuals in extensive reading activities. This study uses a qualitative approach by conducting Semi-structured interviews, with the  hope  of  being  able  to  obtain  in-depth  results  related  to  their  experiences. The study presents comprehensive findings obtained from a series of in-depth interviews to identify students' practices in exploring digital comics in extensive reading and to identify the perceived benefits of using digital comics for extensive reading among EFL students. Interviews were conducted with 10 students who were active members of the English Club and regularly involved in extensive reading activities. In this study, researcher get data from the interviews to find out their extensive reading practices and benefit from extensive reading activities.